2021
DOI: 10.1186/s12984-021-00911-6
|View full text |Cite
|
Sign up to set email alerts
|

A day in the life: a qualitative study of clinical decision-making and uptake of neurorehabilitation technology

Abstract: Background Neurorehabilitation engineering faces numerous challenges to translating new technologies, but it is unclear which of these challenges are most limiting. Our aim is to improve understanding of rehabilitation therapists’ real-time decision-making processes on the use of rehabilitation technology (RT) in clinical treatment. Methods We used a phenomenological qualitative approach, in which three OTs and two PTs employed at a major, technolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…26 In addition, the clinicians in this study expressed a preference for using devices their clients could access at home, such as traditional gait trainers. Other studies of the uptake of neurorehabilitation technology have found therapists preferred practicing functional activities using familiar objects like toothbrushes and silverware, 6 and the unavailability of a device after discharge is a significant barrier to technology use in stroke rehabilitation. 27 While these two studies considered only therapists' perspectives, the current study also gathered data from caregivers who make decisions about their children's therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In addition, the clinicians in this study expressed a preference for using devices their clients could access at home, such as traditional gait trainers. Other studies of the uptake of neurorehabilitation technology have found therapists preferred practicing functional activities using familiar objects like toothbrushes and silverware, 6 and the unavailability of a device after discharge is a significant barrier to technology use in stroke rehabilitation. 27 While these two studies considered only therapists' perspectives, the current study also gathered data from caregivers who make decisions about their children's therapy.…”
Section: Discussionmentioning
confidence: 99%
“…11 It has been applied in various disciplines, including rehabilitation. 6,12 The CFIR consists of 39 constructs, which can be barriers or facilitators, organized into the following five domains: intervention characteristics, characteristics of individuals, inner setting, outer setting, and implementation process. The comprehensive list of constructs without pre-established hypotheses in the CFIR is preferable to an individual framework in this study because the implementation of RAGT in pediatric therapy is relatively uninvestigated.…”
Section: What Is Newmentioning
confidence: 99%
“…In addition, the robot should be able to provide these therapy forms meaningfully over the whole rehabilitation process, e.g., from severely affected to mildly affected [13].…”
Section: A Performance Goals For Clinical Adoptionmentioning
confidence: 99%
“…Further, the robot should be well accessible for all patients, i.e., easy donning and doffing. Additionally, the attachment mechanism has to be efficient to use for the therapist and ergonomic for the patients [13] to achieve a high acceptance by the end-users. The robot should sufficiently support all human upper extremity segments to prevent excessive misalignment and pulling on joints.…”
Section: E Human-robot Attachmentmentioning
confidence: 99%
See 1 more Smart Citation